THE IMPORTANT ROLE OF METACOGNITIVE STRATEGIES IN INDONESIAN EFL READING LEARNING CONTEXTS - Wijaya, Kristian Florensio; Mbato, Concilianus Laos (UC Journal: ELT, Linguistics and Literature Journal, 2022)
It is decent to be purported here that the continual and precise internalization of metacognitive strategies in Indonesian EFL reading contexts will bring about positive influential impacts for L2 readers’ cognitive and affective reading development. Highly metacognitive L2 readers generally experience more stress-free and meaningful reading learning enterprises since they have become more critical, self-regulated, independent, and adaptable readers who are resistant to exacting reading learning challenges. This present qualitative study employed a document analysis approach to strongly encourage Indonesian EFL educationalists to steadily implement metacognitive strategies in their multivariate reading classroom vicinities. The obtained results uncovered that metacognitive reading strategies progressively transfigured Indonesian EFL learners into more self-regulated and autonomous L2 readers longing to inherent life-long second language learning spirit on their daily basis as academicians.